5G beamforming techniques - Nang Kyu Kyu Win (Nanyang Technological University, 2023)
This report presents the main characteristics and motivations for the 5G technology developments and compares them with the previous generations of cellular networks. Some of the emerging research issues are discussed associated with network architecture, frequency band, and bandwidth. Also, the report presents the deployment of new technologies such as MIMO and beam forming. The need for higher data rates, higher flow, high spectral efficiency, a simpler network architecture, and many required services by users has led to new technologies. In the last forty years, significant changes have been in the field of telecommunications. 5G technology has expanded this landscape to provide a wide range of wireless services to facilitate the users through various multiple access platforms and networks. All wireless technologies have contributed to delivering the best voice and data quality for the consumers. However, significant contributions made in recent years to facilitate the communications field for high data connectivity applications. The technological advances of 5G technology will make things possible that were not possible before. Self-driving cars, virtual reality games, smart cities, and the IoT are just a few examples of futuristic breakthroughs with great advantages over the bandwidth and latency improvements this technology will provide very soon. As with any advancement in functional capability, the potential of 5G technology will generate more creativity and a continual flow of new applications. In 5G many networks allow much greater distribution of antenna and much greater centralisation of baseband functionality.